Oncogenic miR-19a and miR-19b co-regulate tumor suppressor MTUS1 to promote cell proliferation and migration in lung cancer. Issue 6 (31st March 2017) - Gu, Yuanyuan; Liu, Shuoxin; Zhang, Xiaodan; Chen, Guimin; Liang, Hongwei; Yu, Mengchao; Liao, Zhicong; Zhou, Yong; Zhang, Chen-Yu; Wang, Tao; Wang, Chen; Zhang, Junfeng; et al.
Abstract: MTUS1 (microtubule-associated tumor suppressor 1) has been identified that can function as a tumor suppressor gene in many malignant tumors. However, the function and mechanisms underlying the regulation of MTUS1 are unclear. In the present study, we reported that miR-19a and miR-19b (miR-19a/b) promote proliferation and migration of lung cancer cells by targeting MTUS1. First, MTUS1 was proved to function as a tumor suppressor in lung cancer and was linked to cell proliferation and migration promotion. Second, an inverse correlation between miR-19a/b expression and MTUS1 mRNA/protein expression was noted in human lung cancer tissues. Third, MTUS1 was appraised as a direct target of miR-19a/b by bioinformatics analysis. Fourth, direct MTUS1 regulation by miR-19a/b in lung cancer cells was experimentally affirmed by cell transfection assay and luciferase reporter assay. Finally, miR-19a/b were shown to cooperatively repress MTUS1 expression and synergistically regulate MTUS1 expression to promote lung cancer cell proliferation and migration. In conclusion, our findings have provided the first clues regarding the roles of miR-19a/b, which appear to function as oncomirs in lung cancer by downregulating MTUS1.